The pioneer woman cooks : the new frontier : 112 fantastic favorites for everyday eating - Drummond, Ree (William Morrow, an imprint of HarperCollinsPublishers, 2019)
Welcome to Ree<U+2019>s new frontier! So much has happened on Drummond Ranch over the last couple of years: The kids are growing up, another left for college, Ree<U+2019>s schedule is crazier than ever<U+2026>and through it all, her cooking has evolved. While she and her family still love all the hearty comfort foods they<U+2019>re accustomed to, Ree<U+2019>s been cooking up some incredible new dishes that reflect the flavors, colors, and texture she<U+2019>s craving these days. The Pioneer Woman Cooks: The New Frontier features 112 brand new step-by-step recipes that bring fresh, exciting elements into your everyday meals. From super-scrumptious breakfasts, to satisfying soups and sandwiches, to deliciously doable suppers and sides<U+2014>and, of course, a collection of irresistible sweets you<U+2019>ll want to make immediately!<U+2014>these pages will deliver a big list of fabulous new dishes for you to add to your repertoire.